The Relationship Of Knowledge And Attitude With Prevention Measures Of Respiratory Functional Disorders In Furniture Workers - Hamdayani Hamdayani; Sri Nurindasari; Fhirawati -; Suandi Suandi; Adnan Adnan; Nur Ilmi (Patria Artha University, 2023)
Health is one of the main priorities of humans in living their lives. Everyone certainly wants to have a healthy and strong body and a good immune system so that they are not susceptible to disease. In factory workers there is a risk of accidents and occupational diseases, which come from various factors such as the work environment. A work environment that is often filled with dust, steam, gas, and others can interfere with health.This study aims to identify the knowledge, attitudes, and efforts of factory workers on respiratory functional disorders of furniture craft workers in Julubori Village, Pallangga District, Gowa Regency in 2022.The design of this research is descriptive with a sample size of 60 people. The data collection tool uses a questionnaire. The data collection technique used is Simple Random Sampling, where the researcher distributes questionnaires directly to the sample in this study.The results of this study indicate that 63.3% of respondents have good knowledge, 73.3% of respondents have a positive attitude. This is due to the influence of the involvement of local health workers who provide counseling to workers who are going well and also factory workers who always use PPE when working. For further research, it is recommended to complete this research by conducting a review of the health of respiratory functional disorders in craftsmen in the village and reviewing the facilities of furniture craftsmen and the condition of furniture craftsmen.